1998
DOI: 10.1523/jneurosci.18-02-00581.1998
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amino Acid Residues of the NR2A Subunit That Control Glutamate Potency in Recombinant NR1/NR2A NMDA Receptors

Abstract: The NMDA type of ligand-gated glutamate receptor requires the presence of both glutamate and glycine for gating. These receptors are hetero-oligomers of NR1 and NR2 subunits. Previously it was thought that the binding sites for glycine and glutamate were formed by residues on the NR1 subunit. Indeed, it has been shown that the effects of glycine are controlled by residues on the NR1 subunit, and a "Venus flytrap" model for the glycine binding site has been suggested by analogy with bacterial periplasmic amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
164
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(183 citation statements)
references
References 32 publications
15
164
2
2
Order By: Relevance
“…Serine to alanine mutations at this position in AMPA and NMDA receptors reportedly has more modest effects on glutamate affinity, and A689S mutation in GluR6 has no affect on glutamate mediated desensitization or 3 H-kainate binding. 22,23,32 In contrast to previous studies examining the reverse mutations in other iGluRs, we found no effect of A518T mutation in GluR6 on glutamate affinity or response kinetics. Neither did the A689S mutation affect these measures.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Serine to alanine mutations at this position in AMPA and NMDA receptors reportedly has more modest effects on glutamate affinity, and A689S mutation in GluR6 has no affect on glutamate mediated desensitization or 3 H-kainate binding. 22,23,32 In contrast to previous studies examining the reverse mutations in other iGluRs, we found no effect of A518T mutation in GluR6 on glutamate affinity or response kinetics. Neither did the A689S mutation affect these measures.…”
Section: Discussioncontrasting
confidence: 99%
“…5 Likewise for NMDA receptors, NR2B-S664G mutation (equivalent to GluR6-A689) reduced glutamate potency by 100-fold relative to wild-type 22 and NR2A-T671A (equivalent to GluR6-T690) reduced glutamate potency by 1000-fold. 23 It is striking, despite the natural substitutions of secondary ligand-binding residues, that AMPA and KARs have similar affinities and exhibit similar, rapidly desensitizing responses to their endogenous agonist, glutamate. Nonetheless, they exhibit significant functional and pharmacological differences.…”
Section: Introductionmentioning
confidence: 99%
“…The residue homologous to GluR2-R485 is perfectly conserved in all AMPA, KA, and NMDA subunits and may be the principal residue to bind during the initial docking step of agonist association (Abele et al, 2000;Armstrong and Gouaux, 2000). Mutagenesis studies confirm the equivalent residue is critical for agonist-induced function in AMPA (Uchino et al, 1992), KA (Ayalon and Stern-Bach, 2001), and NMDA (Laube et al, 1997;Anson et al, 1998) receptors. The residue homologous to GluR2-T655 is also conserved in AMPA, KA, and NMDA subunits, except KA1, which substitutes a serine, and NR1, which substitutes a valine at this position and confers its altered selectivity for glycine (Furukawa and Gouaux, 2003).…”
Section: Glur6-binding Residuesmentioning
confidence: 94%
“…The residue homologous to GluR2-T655 is also conserved in AMPA, KA, and NMDA subunits, except KA1, which substitutes a serine, and NR1, which substitutes a valine at this position and confers its altered selectivity for glycine (Furukawa and Gouaux, 2003). The T655 interaction with agonist is underscored by alanine mutagenesis studies of both AMPA and NR2 receptors (Anson et al, 1998;Lampinen et al, 2002). Likewise, the residue homologous to GluR2-E705 is perfectly conserved in all AMPA and KA subunits and is critical to agonist-receptor interactions in AMPA receptors (Mano et al, 1996;Lampinen et al, 1998;Abele et al, 2000).…”
Section: Glur6-binding Residuesmentioning
confidence: 99%
“…In contrast, the mutation T677A strongly affected the binding of all three agonists. The side chain of this threonine has direct hydrogen bonding interactions with the agonists, and noticeable effects on agonist affinities by mutations at the corresponding residue have been reported previously (6,23).…”
Section: Resultsmentioning
confidence: 65%